COGNITIVE BEHAVIORAL THERAPY TO REDUCE ANXIETY IN FIBROADENOMA MAMMAE PATIENT (CASE STUDY) - Ditsar Ramadhan (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2020)
Case study was conduct to a 30-year-old woman with a diagnose of Illness Anxiety Disorder. Subject complained of experiencing anxiety since being diagnosed with Fibroadenoma Mammae (FAM). She was not enough to be able to accept of doctorâ€™s explanation regarding her condition of benign breast tumor caused by excess hormones from her birth control pill consumed. She always thinks of having a malignant breast tumor which make her dying process faster, this thought more repetitive and settled when she alone. She had medical history of surgical to remove her FAM in 2008. In 2010 she tried to check again, although declared by doctor it was clean, she still felt anxious about her condition. Psychological assessment involves of interviews, observation and psychological tests. The result can be drawn such require of intervention related with her cognitive distortion. The intervention given in this case was cognitive behavioral therapy aimed to reduce her anxiety while changing her cognitive distortion too which was done in 4 sessions. She reported about her progress and decreased of anxiety after therapy.Keywords:Â cognitive behavior therapy, anxiety, FAM.